Antibacterial activity of Laja Gowah (Alpinia malaccensis (Brum.f) Roscoe) oil in Reducing the Number of Staphylococcus aureus Colonies in Hospital Wards - Khoirun Nisyak (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Staphylococcus aureus is one of the pathogenic bacteria that cause nosocomial infections in hospitals. The use of essential oil-based antibacterials for hospital wards was developed to prevent nosocomial infections. Laja gowah oil is an essential oil isolated from the Alpinia malaccensis plant, which belongs to the Zingiberaceae plant group. The purpose of this study was to determine the antibacterial activity of laja gowah oil in reducing the number of S. aureus colonies in hospital inpatient rooms through the air diffusion method. The compound content in laja gowah oil was analyzed with GC-MS. The study of antibacterial activity using the total plant counts continued with the colony count test, Gram staining, catalase test, and coagulase test. Laja gowah oil contains methyl cinnamate and 1,8-cineole. The installation time of the diffuser containing laja gowah oil affects the number of colonies of S. aureus bacteria in hospital wards. The antibacterial activity of laja gowah oil was influenced by the synergistic effect of methyl cinnamate and 1,8-cineole compounds.